White matter changes in recovered COVID-19 patients: insights from DTI, DKI, and NODDI metrics - Yuan, Manxi; Lu, Ruiqi; Liu, Yu; Zhu, Hui; Wang, Hao; Wang, Jingzhi; Song, Yang; Yang, Lei; Xiao, Mingzhong (Frontiers in Neurology, 2025)
BackgroundCOVID-19 affects not only the respiratory system but also the central nervous system, resulting in symptoms such as anosmia and confusion. Understanding the long-term neurological effects of COVID-19 is critical for comprehensive patient care and management.PurposeTo study the long-term neurological effects of COVID-19, focusing on changes in white matter structural complexity using advanced neuroimaging techniques.MethodsThirty-eight participants including 22 recovered COVID-19 patients and 16 healthy controls, underwent MRI scans with T1-weighted, T2-weighted, and diffusion-weighted imaging. Advanced diffusion sequences, including diffusion tensor imaging (DTI), diffusion kurtosis imaging (DKI), and neurite orientation dispersion and density imaging (NODDI), were used to assess microstructural integrity.ResultsSignificant differences in DKI metrics were observed, particularly in mean kurtosis (MK) and radial kurtosis (RK). Reduced MK and RK values were observed in certain regions, particularly the right inferior fronto-occipital fasciculus (IFOF), indicating reduced structural complexity of the white matter. No significant differences in DTI and NODDI metrics or clinical and demographic characteristics were found between the groups.ConclusionThis study highlights the potential long-term neurological sequelae in recovered COVID-19 patients as evidenced by changes in white matter structural complexity. These findings underscore the importance of continued monitoring and tailored interventions to address neurological sequelae as part of the post-COVID-19 recovery process.